1996
DOI: 10.1080/00207149608416083
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and hypnotic preparation for anesthesia and surgery: An individual diferences perspective1

Abstract: Multiple reviews indicate that psychological preparation for surgery can provide psychological, physiological, and economic benefit to the patient. Research demonstrating that hypnosis adds to this benefit is both limited and encouraging. The content and status of this literature, however, are confusing, with little coherent theoretical basis to account for the contradictions and inconsistencies across multiple studies whose methodologies often limit generalization. A model is presented regarding pertinent ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 44 publications
0
7
0
1
Order By: Relevance
“…Asubstantial clinical literature has indicated that hypnosis is an effective tool for managing surgical side effects of a variety of other types of surgery (for reviews, see Blankfield, 1991;Finkelstein, 1991;Gravitz, 1988;Kessler & Dane, 1996;Milling & Costantino, 2000;Pinnell, & Covino, 2000;Wood & Hirschberg, 1994). For example, individual studies have demonstrated that hypnosis is effective for reducing postoperative nausea and vomiting in gynecological and elective surgery patients (Faymonville et al, 1995;Williams, Hind, & Sweeny, 1994), emotional distress in dental and coronary patients (Ashton et al, 1995(Ashton et al, , 1997Enqvist, von Konow, & Bystedt, 1995), pain in abdominal and dental patients (Egbert, Battit, &Welch, 1964;Enqvist & Fischer, 1997), and time to discharge in a variety of surgical patients (Bonke, Schmitz, Verhage, & Zwaveling, 1986;Evans & Richardson, 1988;Pearson, 1961;Raplun, Straubing, & Holroyd, 1991).…”
mentioning
confidence: 99%
“…Asubstantial clinical literature has indicated that hypnosis is an effective tool for managing surgical side effects of a variety of other types of surgery (for reviews, see Blankfield, 1991;Finkelstein, 1991;Gravitz, 1988;Kessler & Dane, 1996;Milling & Costantino, 2000;Pinnell, & Covino, 2000;Wood & Hirschberg, 1994). For example, individual studies have demonstrated that hypnosis is effective for reducing postoperative nausea and vomiting in gynecological and elective surgery patients (Faymonville et al, 1995;Williams, Hind, & Sweeny, 1994), emotional distress in dental and coronary patients (Ashton et al, 1995(Ashton et al, , 1997Enqvist, von Konow, & Bystedt, 1995), pain in abdominal and dental patients (Egbert, Battit, &Welch, 1964;Enqvist & Fischer, 1997), and time to discharge in a variety of surgical patients (Bonke, Schmitz, Verhage, & Zwaveling, 1986;Evans & Richardson, 1988;Pearson, 1961;Raplun, Straubing, & Holroyd, 1991).…”
mentioning
confidence: 99%
“…She can be helped to transform the experience of an office visit or procedure into one of actively caring for herself. Hypnosis can be used to enhance coping, utilizing awareness of the patient's preferred coping style, for example, by checking on whether the woman has all the information she needs to make her decisions (e.g., Kessler and Dane, 1996). Many women's sensitivity to the needs of the other can be utilized, by suggesting that the doctor wants to do the best possible job and that her questions and her thorough understanding of what is said will help the doctor as well as herself.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, a resurgence in the use of hypnotherapy and increased acceptance of hypnotherapy as a treatment modality in surgery is evident (Blankfield, 1991;Evans & Stanley, 1990, 1991Fredericks, 2000Fredericks, , 2001Kessler & Dane, 1996;01ness & Kohen, 1996;Pinnell & Covino, 2000;Sunnen, 2000;Varga & Dioszeghy, 2003). Hypnotherapeutic interventions have been used with hospitalized patients undergoing orthopedic, plastic, pediatric, obstetrical, gynecological, oncological, and general surgery (Fredericks, 2001;Manusov, 1990;Olness & Kohen, 1996).…”
Section: Hypnotherapeutic Ego Strengtheningmentioning
confidence: 92%